Examples
xq(x)11223344xq(x)11223344
Step 1
Step 1.1
To find if the table follows a function rule, check to see if the values follow the linear form y=ax+by=ax+b.
y=ax+by=ax+b
Step 1.2
Build a set of equations from the table such that q(x)=ax+bq(x)=ax+b.
1=a(1)+b2=a(2)+b3=a(3)+b4=a(4)+b
Step 1.3
Calculate the values of a and b.
Step 1.3.1
Solve for a in 1=a+b.
Step 1.3.1.1
Rewrite the equation as a+b=1.
a+b=1
2=a(2)+b
3=a(3)+b
4=a(4)+b
Step 1.3.1.2
Subtract b from both sides of the equation.
a=1-b
2=a(2)+b
3=a(3)+b
4=a(4)+b
a=1-b
2=a(2)+b
3=a(3)+b
4=a(4)+b
Step 1.3.2
Replace all occurrences of a with 1-b in each equation.
Step 1.3.2.1
Replace all occurrences of a in 2=a(2)+b with 1-b.
2=(1-b)(2)+b
a=1-b
3=a(3)+b
4=a(4)+b
Step 1.3.2.2
Simplify the right side.
Step 1.3.2.2.1
Simplify (1-b)(2)+b.
Step 1.3.2.2.1.1
Simplify each term.
Step 1.3.2.2.1.1.1
Apply the distributive property.
2=1⋅2-b⋅2+b
a=1-b
3=a(3)+b
4=a(4)+b
Step 1.3.2.2.1.1.2
Multiply 2 by 1.
2=2-b⋅2+b
a=1-b
3=a(3)+b
4=a(4)+b
Step 1.3.2.2.1.1.3
Multiply 2 by -1.
2=2-2b+b
a=1-b
3=a(3)+b
4=a(4)+b
2=2-2b+b
a=1-b
3=a(3)+b
4=a(4)+b
Step 1.3.2.2.1.2
Add -2b and b.
2=2-b
a=1-b
3=a(3)+b
4=a(4)+b
2=2-b
a=1-b
3=a(3)+b
4=a(4)+b
2=2-b
a=1-b
3=a(3)+b
4=a(4)+b
Step 1.3.2.3
Replace all occurrences of a in 3=a(3)+b with 1-b.
3=(1-b)(3)+b
2=2-b
a=1-b
4=a(4)+b
Step 1.3.2.4
Simplify the right side.
Step 1.3.2.4.1
Simplify (1-b)(3)+b.
Step 1.3.2.4.1.1
Simplify each term.
Step 1.3.2.4.1.1.1
Apply the distributive property.
3=1⋅3-b⋅3+b
2=2-b
a=1-b
4=a(4)+b
Step 1.3.2.4.1.1.2
Multiply 3 by 1.
3=3-b⋅3+b
2=2-b
a=1-b
4=a(4)+b
Step 1.3.2.4.1.1.3
Multiply 3 by -1.
3=3-3b+b
2=2-b
a=1-b
4=a(4)+b
3=3-3b+b
2=2-b
a=1-b
4=a(4)+b
Step 1.3.2.4.1.2
Add -3b and b.
3=3-2b
2=2-b
a=1-b
4=a(4)+b
3=3-2b
2=2-b
a=1-b
4=a(4)+b
3=3-2b
2=2-b
a=1-b
4=a(4)+b
Step 1.3.2.5
Replace all occurrences of a in 4=a(4)+b with 1-b.
4=(1-b)(4)+b
3=3-2b
2=2-b
a=1-b
Step 1.3.2.6
Simplify the right side.
Step 1.3.2.6.1
Simplify (1-b)(4)+b.
Step 1.3.2.6.1.1
Simplify each term.
Step 1.3.2.6.1.1.1
Apply the distributive property.
4=1⋅4-b⋅4+b
3=3-2b
2=2-b
a=1-b
Step 1.3.2.6.1.1.2
Multiply 4 by 1.
4=4-b⋅4+b
3=3-2b
2=2-b
a=1-b
Step 1.3.2.6.1.1.3
Multiply 4 by -1.
4=4-4b+b
3=3-2b
2=2-b
a=1-b
4=4-4b+b
3=3-2b
2=2-b
a=1-b
Step 1.3.2.6.1.2
Add -4b and b.
4=4-3b
3=3-2b
2=2-b
a=1-b
4=4-3b
3=3-2b
2=2-b
a=1-b
4=4-3b
3=3-2b
2=2-b
a=1-b
4=4-3b
3=3-2b
2=2-b
a=1-b
Step 1.3.3
Solve for b in 4=4-3b.
Step 1.3.3.1
Rewrite the equation as 4-3b=4.
4-3b=4
3=3-2b
2=2-b
a=1-b
Step 1.3.3.2
Move all terms not containing b to the right side of the equation.
Step 1.3.3.2.1
Subtract 4 from both sides of the equation.
-3b=4-4
3=3-2b
2=2-b
a=1-b
Step 1.3.3.2.2
Subtract 4 from 4.
-3b=0
3=3-2b
2=2-b
a=1-b
-3b=0
3=3-2b
2=2-b
a=1-b
Step 1.3.3.3
Divide each term in -3b=0 by -3 and simplify.
Step 1.3.3.3.1
Divide each term in -3b=0 by -3.
-3b-3=0-3
3=3-2b
2=2-b
a=1-b
Step 1.3.3.3.2
Simplify the left side.
Step 1.3.3.3.2.1
Cancel the common factor of -3.
Step 1.3.3.3.2.1.1
Cancel the common factor.
-3b-3=0-3
3=3-2b
2=2-b
a=1-b
Step 1.3.3.3.2.1.2
Divide b by 1.
b=0-3
3=3-2b
2=2-b
a=1-b
b=0-3
3=3-2b
2=2-b
a=1-b
b=0-3
3=3-2b
2=2-b
a=1-b
Step 1.3.3.3.3
Simplify the right side.
Step 1.3.3.3.3.1
Divide 0 by -3.
b=0
3=3-2b
2=2-b
a=1-b
b=0
3=3-2b
2=2-b
a=1-b
b=0
3=3-2b
2=2-b
a=1-b
b=0
3=3-2b
2=2-b
a=1-b
Step 1.3.4
Replace all occurrences of b with 0 in each equation.
Step 1.3.4.1
Replace all occurrences of b in 3=3-2b with 0.
3=3-2⋅0
b=0
2=2-b
a=1-b
Step 1.3.4.2
Simplify the right side.
Step 1.3.4.2.1
Simplify 3-2⋅0.
Step 1.3.4.2.1.1
Multiply -2 by 0.
3=3+0
b=0
2=2-b
a=1-b
Step 1.3.4.2.1.2
Add 3 and 0.
3=3
b=0
2=2-b
a=1-b
3=3
b=0
2=2-b
a=1-b
3=3
b=0
2=2-b
a=1-b
Step 1.3.4.3
Replace all occurrences of b in 2=2-b with 0.
2=2-(0)
3=3
b=0
a=1-b
Step 1.3.4.4
Simplify the right side.
Step 1.3.4.4.1
Subtract 0 from 2.
2=2
3=3
b=0
a=1-b
2=2
3=3
b=0
a=1-b
Step 1.3.4.5
Replace all occurrences of b in a=1-b with 0.
a=1-(0)
2=2
3=3
b=0
Step 1.3.4.6
Simplify the right side.
Step 1.3.4.6.1
Subtract 0 from 1.
a=1
2=2
3=3
b=0
a=1
2=2
3=3
b=0
a=1
2=2
3=3
b=0
Step 1.3.5
Remove any equations from the system that are always true.
a=1
b=0
Step 1.3.6
List all of the solutions.
a=1,b=0
a=1,b=0
Step 1.4
Calculate the value of y using each x value in the relation and compare this value to the given q(x) value in the relation.
Step 1.4.1
Calculate the value of y when a=1, b=0, and x=1.
Step 1.4.1.1
Multiply 1 by 1.
y=1+0
Step 1.4.1.2
Add 1 and 0.
y=1
y=1
Step 1.4.2
If the table has a linear function rule, y=q(x) for the corresponding x value, x=1. This check passes since y=1 and q(x)=1.
1=1
Step 1.4.3
Calculate the value of y when a=1, b=0, and x=2.
Step 1.4.3.1
Multiply 2 by 1.
y=2+0
Step 1.4.3.2
Add 2 and 0.
y=2
y=2
Step 1.4.4
If the table has a linear function rule, y=q(x) for the corresponding x value, x=2. This check passes since y=2 and q(x)=2.
2=2
Step 1.4.5
Calculate the value of y when a=1, b=0, and x=3.
Step 1.4.5.1
Multiply 3 by 1.
y=3+0
Step 1.4.5.2
Add 3 and 0.
y=3
y=3
Step 1.4.6
If the table has a linear function rule, y=q(x) for the corresponding x value, x=3. This check passes since y=3 and q(x)=3.
3=3
Step 1.4.7
Calculate the value of y when a=1, b=0, and x=4.
Step 1.4.7.1
Multiply 4 by 1.
y=4+0
Step 1.4.7.2
Add 4 and 0.
y=4
y=4
Step 1.4.8
If the table has a linear function rule, y=q(x) for the corresponding x value, x=4. This check passes since y=4 and q(x)=4.
4=4
Step 1.4.9
Since y=q(x) for the corresponding x values, the function is linear.
The function is linear
The function is linear
The function is linear
Step 2
Since all y=q(x), the function is linear and follows the form y=x.
y=x